Critical-Collaborative Learning Model on Socioscientific Issues: Impact on Critical Thinking Skills of Pre-Service Teachers - Irwandani*, Irwandani; Aridan, Muhammad; Barata, Muhammad Farhan; Susilowati, Nur Endah; Villarama, Joseph Agbuya (Universitas Syiah Kuala, 2025)
This study investigates the impact of the critical-collaborative learning model (CCLM), which integrates socioscientific issues within a problem-based learning framework, on enhancing the critical thinking skills (CTS) of pre-service physics teachers. A quasi-experimental design with non-equivalent control groups was employed, with 26 students in the experimental group and 27 students in the control group. The experimental group, which engaged in project-based learning activities centered on real-world issues such as climate change and energy crises, demonstrated significant improvements in CTS, as measured by the Rasch model. The pretest mean logit for the experimental group was 125.25 (SD = 72.24), and after the intervention, the posttest mean logit was 77.69 (SD = 3.87), showing a significant improvement with a gain of -47.56. In contrast, the control group showed a smaller change, with a pretest mean logit of 66.92 (SD = 45.28) and a posttest mean logit of 50.23 (SD = 80.57), resulting in a smaller gain of -16.68. The findings suggest that incorporating collaborative and socioscientific elements into the learning process fosters deeper engagement and higher-order thinking. This study contributes to the body of research supporting constructivist-based and collaborative learning approaches, offering valuable insights into their application in science education. Further investigation into the long-term effects of such models across diverse educational contexts is recommended